On the class of limit distributions for thinning currents of homogeneous events - Kovalenko, I. N. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Н. Коваленко, О классе предельных распределений для редеющих потоков однородных событий I. N. Kovalenko, Apie homogeninių įvykių retėjančių srautų ribinių pasiskirstymų klasę